Participatory Evaluation of Sorghum Processing and Sensory Attributes in Mali: Methodology for Improving Food Security Outcomes from Variety Development Efforts - Krista Isaacs; Marjolein Smit; Bakary Samaké; Fred Rattunde; Fatimata Cissé; Abdoulaye Diallo; Mamourou Sidibe; Eva Weltzien (MDPI, 2023)
A requirement for the successful development of new sorghum varieties in Mali is effective evaluation of grain qualities, since sorghum is a staple food crop on which farmers rely for food security. The diversity of grain quality and social aspects that determine varietal acceptability for processing and cooking, however, make this a challenging task. As the processors of sorghum grain in households, women’s knowledge of grain quality traits can contribute to this work. Our objective is to understand opportunities to use grain quality traits to identify experimental varieties that may contribute to food security. Culinary evaluations were conducted in nine villages across two sorghum production zones. Three teams of women, one per replicate, processed, cooked and evaluated five test varieties in each village. Sensory evaluations were conducted by 25 taste testers per village. The major varietal differences observed included the decortication losses, women’s appreciation for ease of processing, and consistency of the prepared food. The participatory evaluation of the quality testing results led to the development of the concept of ‘food yield’. Discussion of these results focuses on designing cost-efficient grain and food quality evaluations that rely on women’s expertise as processors and strengthens their role in the variety development process.